Hadith #561 - Sunan al-Nasa'i - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Shu'aib bin Shu'aib bin Ishaq شعيب بن شعيب بن إسحاق (Sunan al-Nasa'i)
“The sun rises and with it the horn of the Shaitan, then when it is fully risen, he goes away. Then when it approaches the meridian he comes near to it, and when it has passed the zenith he goes away. Then when it is close to setting, he comes near to it, then when it has set, he goes away.” And the Messenger of Allah (ﷺ) forbade praying at those times.
Grade:

Hadith #1766 - Sunan al-Nasa'i - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Hafsa bint Umar; ibn Umar; Nafie' نافع مولى ابن عمر; Shu'aib bin Abi Hamza شعيب بن أبي حمزة; Shu'aib bin Shu'aib bin Ishaq شعيب بن شعيب بن إسحاق; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“Hafsah told me that when dawn glowed, the Prophet (ﷺ) would pray two rak’ahs.
Grade:

Hadith #2258 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Jabir ibn 'Abdullah; Muhammad bin 'Abdur Rahman محمد بن عبد الرحمن بن نوفل; Shu'aib bin Abi Hamza شعيب بن أبي حمزة; Shu'aib bin Shu'aib bin Ishaq شعيب بن شعيب بن إسحاق; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
“The Messenger of Allah said: Whoever fasts a day in the cause of Allah, Allah will separate his face (a distance of) seventy autumns from the fire in return for that day.”
Grade:

Hadith #2271 - Sunan al-Nasa'i - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Shu'aib bin Abi Hamza شعيب بن أبي حمزة; Shu'aib bin Shu'aib bin Ishaq شعيب بن شعيب بن إسحاق; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan al-Nasa'i)
That the Messenger of Allah , Abu Bakr and ‘Umar were in Marr Az-Zahran. He narrated it in Mursal from. (Daif)
Grade:

Hadith #2841 - Sunan al-Nasa'i - Abdul Quddus bin al-Hajjaj al-Khulani عبد القدوس بن الحجاج الخولاني; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Ata' bin Abi Rabah عطاء بن أبي رباح; ibn Abbas; Safwan bin 'Amr صفوان بن عمرو; Shu'aib bin Shu'aib bin Ishaq شعيب بن شعيب بن إسحاق (Sunan al-Nasa'i)
“The Prophet said: ‘There are five kinds of animals for which there is no sin on the one who kills them, whether he is in Ihram or not: Mice, kites, crows, scorpions and vicious dogs.'”
Grade:

Hadith #5155 - Sunan al-Nasa'i - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Shu'aib bin Abi Hamza شعيب بن أبي حمزة; Shu'aib bin Shu'aib bin Ishaq شعيب بن شعيب بن إسحاق (Sunan al-Nasa'i)
“The Prophet of Allah took hold of some silk in his right hand, and some gold in his left, then he said: ‘These two are forbidden for the males of my Ummah.'”
Grade: